Changes in physicochemical quality and protein properties of porcine longissimus lumborum during dry ageing. (8th July 2022) - Wang, Hengpeng; Wang, Yinlan; Wu, Danxuan; Gao, Sumin; Jiang, Songsong; Tang, Hailian; Lv, Guanhua; Zou, Xiaobo; Meng, Xiangren
Summary: The present study investigated the effects of dry‐ageing time on physicochemical quality and protein properties of porcine longissimus lumborum within 48 h of postmortem ageing. Results showed that appropriately prolonged dry‐ageing time (24 and 36 h) had a positive effect on the tenderness, water‐holding capacity, thermal stability and gel properties of meat, as evident from the decrease of shear force, dripping loss, cooking loss, T 2 relaxation time, enthalpy value and the increase in storage and loss modulus. Nevertheless, the excessive extension of ageing (48 h) increased the degree of protein oxidation and degradation by maintaining the lowest total sulfhydryl but the highest carbonyl content, and producing more small molecular weight protein chains (35.4, 20 and 19.6 KDa). Chemometric analysis further clarified the appropriate ageing time of desirable meat. In conclusion, dry ageing 24 and 36 h were suggested as the reasonable postmortem ageing time for porcine longissimus lumborum in China. Abstract : The porcine longissimus lumborum dry‐aged 24 and 36 h could obtain better qualities by improving tenderness, colour, gelation behaviour, water‐holding capacity and decreasing protein oxidation. From the perspective of time and economic cost, dry ageing 24 h was recommended as the most suitable postmortem time for longissimus lumborum of Chinese typical hybrid pigs.